Development of a binary carrier system consisting polyethylene glycol 4000 - ethyl cellulose for ibuprofen solid dispersion - Algadar, Gada Sulaiman; May, Kyaw Oo; Sengupta, Pinaki Ranjan; Mandal, Uttam Kumar; Md. Jaffri, Juliana; Chatterjee, Bappaditya (Wolters Kluwer, 2017)
Background and Objective: One of the established strategies to improve solubility and dissolution rate of poorly water-soluble drugs is solid dispersion (SD). Polyethylene glycol (PEG) is used as common carrier despite its stability problem which may be overcome by the addition of hydrophobic polymer. The present research aims to develop an SD formulation with ibuprofen, a poor water-soluble BCS Class II drug as active pharmaceutical ingredient (API) and PEG 4000-ethyl cellulose (EC) as binary carrier. Methods: Melt mixing SD method was employed using a ratio of API: binary carrier (1:3.5 w/w) (SDPE). Another SD was prepared using only PEG (SDP) as a carrier for comparative study. The developed formulation was evaluated using optical microscopy, scanning electron microscopy (SEM), determination of moisture content, differential scanning calorimetry (DSC), in vitro dissolution test, attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) and flow properties. Results: SEM and DSC indicated the conversion of crystalline ibuprofen to fine partly amorphous solid dispersion, which is responsible for the increase in dissolution rate of SD than a physical mixture. The release characteristics within 1 h from the higher to the lower value were the SDPE > SDP > physical mixture. Flow property evaluation using the angle of repose showed no difference between SD and PM. However, by Carr index and Hausner ratio, the flow properties of SDPE was excellent. Conclusion: The SD formulation with the PEG 4000-EC carrier can be effective to enhance in vitro dissolution of ibuprofen immediate release dosage form.